Las facies carbonatadas del Trias medio de La Formación Hornos-Siles (provincia de Jaén, Zona Prebética) - Hirsch, F.; Fernández Turiel, J.L.; García-hernández, M.; Gil, A.; López-garrido, A.C. (Cuadernos de Geología Ibérica, 1987)
Sin resumen